الأفكار المشبوهة حول دراسة النسخ في علوم القرآن: التعليقات والتعقيبات - Husni Mubarrak (Universitas Darussalam Gontor, 2016)
This article discusses naskh in the studies of the Qur’an (‘Ulûm al-Qur’ân). The research focus begins on different understandings and interpretations on stoning punishment for adulterers who had married, based on the story of a Prophet’s companion, Umar ibn Khattab, who said that it was a part of the Qur’an until it then removed from the Qur’an, even though the law is still in force. This story is often used as an example of a naskh criteria that the script had been removed from the Qur’an, even though the law remains in force which were frequently targeted as a form of negligence and mistakes that (probably) there are parts of the Qur’an forgotten, missed or even disappeared when the collecting and codifying the Qur’an in the Ṣaḥâbah (Companions) period since the era of Abu Bakar up to Utsman ibn ‘Affan. These diverse understandings and various thinking related to naskh in al-Qur’an are awkward things which are strongly influenced by orientalism mind and thinking that then come to the surface until, in turn, led to doubt on the validity of the Qur’an that exist today until arousing some efforts to reconstruct and reorder the Qur’an based on corresponding period. This article is quietly concerned to criticize and straighten naskh understanding of the Qur’an with reference to the main reference (mother books) in the tradition of ‘Ulûm al-Qur’ân (Turâts) which are valid and can be justified scientifically.